The effect of age and material on the deterioration of chlorine separation in the water supply network using the qualitative-hydraulic model EPANET (II) - Maryam Siamaki; Omid Zabihi; Reza Aghlmand; Mohammad Gheibi (Annals of Systems Biology - Peertechz Publications, 2021)
According to international and domestic standards, the concentration of free chlorine remaining in each node must be between certain values. In this way, the health of the water is guaranteed. Water sources are chlorinated after treatment and enter the water distribution network. Injected chlorine is reduced in this path by reacting with materials in the water (mass deterioration) and the distribution network pipe wall (wall decay). Meanwhile, wall deterioration is a function of the age and material of the pipe. This study evaluated the pipe material parameter among the group of PVC and cast iron pipes. Also, to investigate the effect of age, the amount of residual free chlorine distribution in cast iron pipes with ages of zero, 10, 20, and 30 years was qualitatively hydraulically simulated. A comparison study showed that the maximum difference in free chlorine concentration in different genera is 17.82% and at different ages is 34.71%.